Improving Studentsâ Writing Achievement ByUsing Collaborative Writing - Manurung, Jenny Elvinna (JURNAL DIDASCEIN BAHASA, 2016)
ABSTRACT:Â  Teaching English for Senior High School involves writing skill though not as much as reading skill. Writing is used to identify, analyze and develop ideas. They must learn how to compose sentences, build texts and express ideas within the standards of written English. However, there are still many students who have low achievement in writing. Therefore, the objective of the study was to find out whether the collaborative writing technique through Facebook could improve students writing skill especially in narrative writing. The randomized control group pretest-posttest design was applied in this study. Forty out of 100 third grade students of SMA Methodist 2 Palembang in academic year 2010/2011 were taken as the sample. There were 3 groups, each of which consisted of 20 students. The obtained data were analyzed using paired sample t-test and independent sample test. The findings showed that there was significant progress in writing achievement of the students who were taught using collaborative writing technique through Facebook.Â Keywords: collaborative writing technique, facebook, improving writingÂ  skill and narrative text.Â Â Â Â